FREE LUNCH FOR STUDENTS IN SEVERAL COUNTRIES AND LESSON LEARNED FOR INDONESIA IN ORDER TO PREPARE FOR THE GOLDEN GENERATION 2045 - K.P.Suharyono Soemarwoto Hadiningrat; Teguh Yuwono (Yayasan Inspirasi Merah Putih Indonesia, 2024)
Human Resources who are physically healthy, spiritual, intelligent and have integrity are an effort of the Republic of Indonesia to promote public welfare and educate the nation's life as stipulated in the Preamble to the 1945 Constitution, must be carried out continuously, comprehensively and continuously. In this case, the strong commitment of the Government of President Prabowo Subiyanto greatly determines the success of Astacita's programs, one of which is a nutritious meal program for students, toddlers and pregnant women. This is a new program, which must be carefully prepared with adequate resource support, including bench marks to take lessons from the success stories of other countries, such as the United States, France, Japan, South Korea and others. The design of this study is qualitative descriptive using secondary data from credible publications, which are analyzed qualitatively to describe the phenomenon of the research variables. The results found that the success of other countries in organizing free lunches for students is a human investment program for the state in preparing superior human resources that have been going on for tens or even hundreds of years, have significant benefits in improving the degree of health, quality of human resources and the economy of the community. It is recommended that Indonesia prepare a nutritious lunch program carefully, both in terms of regulations/laws, institutions, human resources to manage, the use of technology and financing so that it is sustainable, not just lasting 5 years.